Crossing Language Borders – as Shown by the Historical Dictionary of the Hungarian Language in Transylvania - Zsemlyei Borbála (Acta Universitatis Sapientiae: Philologica, 2017)
Transylvania has always been a space of multiculturalism, which is reflected in the fact that the Hungarian regional standard contains more Romanian and German elements than the central standard. And that is not only peculiar to the present state of the language, but it is a historical phenomenon. During the process of editing the Historical Dictionary of the Hungarian Language in Transylvania, Attila Szabó T. and his co-workers realized that the language material gathered from Transylvanian archives contains a number of Hungarian words of Romanian origin that the literature has no knowledge of. Thus came the idea of a smaller dictionary which would present the Romanian loan words of Hungarian spoken in Transylvania in the period of the 16th–19th centuries. By the mid-1980s, the editorial work was finalized; however, it has never been published – the material is kept at the Department of Hungarian and General Linguistics, Babeş–Bolyai University, Cluj-Napoca. In my paper, I will attempt to present the words of Romanian origin listed in the Historical Dictionary of the Hungarian Language in Transylvania, which the general literature of loan words has no knowledge of in the context of crossing borders, in the sense that neighbouring languages always have a huge impact on each other even if they are completely different genetically.